2010
DOI: 10.1002/ijc.25265
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of specific KRAS mutation, BRAF and microsatellite instability identifies prognostic subgroups of sporadic and hereditary colorectal cancer

Abstract: Confounding effects of specific KRAS gene alterations on colorectal cancer (CRC) prognosis stratified by microsatellite instability (MSI) and BRAF V600E have not yet been investigated. The aim of our study was to evaluate the combined effects of MSI, BRAF V600E and specific KRAS mutation (Gly fi Asp; G12D, Gly fi Asp, G13D; Gly fi Val; G12V) on prognosis in 404 sporadic and 94 hereditary CRC patients. MSI status was determined according to the Bethesda guidelines. Mutational status of KRAS and BRAF V600E was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 35 publications
5
55
1
9
Order By: Relevance
“…There are several reports with similar results for the frequency of the BRAF mutation in MSI and MSS cancers (29)(30)(31). Lubomierski et al (31) suggested that there were two genetically distinct entities of MSI cancer with and without the BRAF mutation, which is consistent with our data.…”
Section: Discussionsupporting
confidence: 82%
“…There are several reports with similar results for the frequency of the BRAF mutation in MSI and MSS cancers (29)(30)(31). Lubomierski et al (31) suggested that there were two genetically distinct entities of MSI cancer with and without the BRAF mutation, which is consistent with our data.…”
Section: Discussionsupporting
confidence: 82%
“…Se ha descrito que la sobrevida de pacientes en etapas tempranas supera 90%, pero en estadios metastásicos es inferior a 10% 30 . En los últimos años, la incorporación de terapias moleculares ha permitido mejorar la sobrevida de estos pacientes, sin embargo, debido a la heterogeneidad de los tumores, no tienen la misma efectividad en todos los pacientes [31][32][33][34] . Considerando lo anterior, el año 2015 se estableció un grupo internacional de subtipificación del CCR , The CRC Subtyping Consortium, basado en datos provenientes de The Cancer Genome Atlas complementados con análisis moleculares y mutacionales 19 .…”
Section: Discussionunclassified
“…The vast majority of the studies investigating B-RAF mutation frequency in different types of cancer, including melanoma and colorectal adenocarcinoma [22][23][24][25][26][27][28][29], focus mainly at the thymine (T) 1799 nucleotide. This is the first study measuring the expression status of B-RAF in TCC of the urinary bladder.…”
Section: Discussionmentioning
confidence: 99%